2015
DOI: 10.1111/cns.12431
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Graph Metrics in High‐resolution Functional Connectomics: A Resting‐State Functional MRI Study

Abstract: We showed high test-retest reliability for graph properties in the high-resolution functional connectomics, which provides important guidance for choosing reliable network metrics and analysis strategies in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 73 publications
8
48
3
Order By: Relevance
“…5,6). These observations converge with previous findings based on resting‐state fMRI [Andellini et al, ; Braun et al, ; Du et al, ; Guo et al, ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5,6). These observations converge with previous findings based on resting‐state fMRI [Andellini et al, ; Braun et al, ; Du et al, ; Guo et al, ].…”
Section: Discussionsupporting
confidence: 93%
“…In general, functional neuroimaging measures during resting‐state condition show moderate test–retest reliability. Consistently with previous reports, ICCs range between fair to good for functional connectivity measures, and good to moderate for graph metrics like degree centrality [Braun et al, ; Cao et al, ; Du et al, ; Guo et al, ; Patriat et al, ; Shehzad et al, ]. To improve the reliability of resting‐state functional measures, previous studies have tested a variety of experimental and analytical strategies.…”
Section: Discussionsupporting
confidence: 81%
“…Using a publicly available dataset from the HCP, we identified a stable small‐world property in voxel‐based functional networks and highly connected hubs located in the DMN, the salience network, the FPN, and the primary visual cortex. These results are consistent with those of previous voxel‐based functional network studies (Du et al, ; Liao et al, ; van den Heuvel & Sporns, ). Significantly higher modularity and BC were observed in the female group mainly in the medial/lateral fronto‐parietal and occipital cortices.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we observed a significant effect of global signal regression on the calculation of network metrics, although both kinds of networks retained predominant small-world and modular architectures. fMRI studies have revealed that functional metrics could be affected by global signal regression for reduced BOLD spectral power and improvement in the detection of system-level correlations in resting-state brain networks (Du et al, 2015;Fox, Zhang, Snyder, & Raichle, 2009;Liang et al, 2012;Liu, Nalci, & Falahpour, 2017). However, the biological mechanism for the global signal remains largely unknown (Murphy & Fox, 2017;Qing, Dong, Li, Zang, & Liu, 2015;Saad et al, 2012;Schwarz & McGonigle, 2011…”
Section: Future Studiesmentioning
confidence: 99%
“…In this issue, Du et al. performed an important resting‐state functional MRI study by systematically evaluating the test–retest reliability of various graph metrics in the high‐resolution (voxel level) functional networks in 53 healthy participants. Specifically, using different nodal metrics, they identified functional hubs of the brain networks mainly located at the default‐mode, salience, and executive control systems.…”
mentioning
confidence: 99%